Surprise! An Investigation of Orienting Responses to Test Assumptions of Narrative Processing - Sukalla, Freya and Shoenberger, Heather and Bolls, Paul D. (Communication Research, 2016)
This study tests theoretical assumptions about how the level of narrative engagement during exposure to a television series storyline influences how viewers process scenes within the storyline. An embodied cognition approach to information processing was applied to record and interpret psychophysiological data reflecting how viewers mentally process television program narratives. Specifically, we recorded physiological data indicating the orienting response (OR) to examine viewers’ processing of narrative surprise structures. In a 4 (storyline) × 4 (order) mixed repeated measures experiment, 59 participants watched four stimulus clips including a surprising plot development while psychophysiological measures were being recorded. After about 4 to 5 minutes into the clip but before the surprising event, they were asked to indicate their level of narrative engagement. Results confirm that surprise structures do elicit ORs in viewers, and they occur regardless of the level of narrative engagement. This study highlights the potential of combining an embodied cognition approach with existing approaches to understanding how viewers process narratives and provides inspiration for future research about narrative processing and persuasion.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwMjE1NTk2MzYz